2018
DOI: 10.1101/243345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Pre-Existing Adaptive Immunity to Cas9 Proteins in Humans

Abstract: The CRISPR-Cas9 system has proven to be a powerful tool for genome editing, allowing for the precise modification of specific DNA sequences within a cell. Many efforts are currently underway to use the CRISPR-Cas9 system for the therapeutic correction of human genetic diseases. The most widely used homologs of the Cas9 protein are derived from the bacteria Staphylococcus aureus (S. aureus) and Streptococcus pyogenes (S. pyogenes). Based on the fact that these two bacterial species cause infections in the human… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 35 publications
3
80
1
2
Order By: Relevance
“…A possible roadblock to effective clinical translation of the CRISPR/Cas9 research revolution is the recent finding that a large proportion of humans have pre-existing immunity to two of the widely-used Cas9 orthologues, saCas9 and spCas9 [99]. The antibody reaction found against both orthologues is troubling for the in-vivo use of ribonucleoprotein (RNP) mixtures of recombinant Cas9 protein and synthetic gRNAs without any form of cloaking.…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…A possible roadblock to effective clinical translation of the CRISPR/Cas9 research revolution is the recent finding that a large proportion of humans have pre-existing immunity to two of the widely-used Cas9 orthologues, saCas9 and spCas9 [99]. The antibody reaction found against both orthologues is troubling for the in-vivo use of ribonucleoprotein (RNP) mixtures of recombinant Cas9 protein and synthetic gRNAs without any form of cloaking.…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…As the CRISPR‐Cas systems are of prokaryotic origin, it remains to be seen whether innate or adaptive immune responses will hinder their clinical application. Both Streptococcus pyogenes and Staphylococcus aureus are human pathogens; preexisting antibodies against the Cas9 proteins from these bacterial species have been identified in humans . The presence of humoral and cell‐mediated immunity to Cas proteins is a challenge but could be mitigated by immunosuppression, limiting exposure to a single dose, and/or using Cas proteins from microbes that humans have not encountered and acquired immunity against .…”
Section: Future Therapeutic Applicationsmentioning
confidence: 99%
“…While awaiting the first news of how CRISPR genome editing performs in the clinic, researchers are working to surmount some of the technique's known limitations. Namely, there is a dearth of sufficient methods for delivering genome‐editing molecules into disease‐affected patient tissues; desired edits must be performed without causing any genetic collateral damage; and the possibility of preexisting immunity or a post‐treatment immune reaction to bacterial CRISPR proteins must be assessed . As some scientists refine the technology and gear up for clinical use, others continue to find novel medical uses for CRISPR enzymes.…”
mentioning
confidence: 99%
“…The authors targeted Cas9 to a binding site for BCL11A within the promoter of γ‐globin and demonstrated efficient switch from human β‐globin to γ‐globin expression in red blood cells. A potential obstacle for human translation is the broad pre‐existing immunity to Cas9 in humans (Charlesworth et al , ; Wagner et al , ), which may be avoided by administration of immunosuppressive drugs. In vivo gene correction or gene insertion would require additional delivery of the DNA repair template and low HR frequencies would be expected in HSCs that have not been stimulated with cytokines, which is standard in ex vivo HSC therapies.…”
Section: Future Directionsmentioning
confidence: 99%